Language approaches to the study of meteorology - Karina Bianca Ioana HAUER (Scientific Bulletin of the Politehnica University of Timişoara: Transactions on Modern Languages)
Meteorology is an important science which has constantly evolved in the last centuries, as people became more and more aware of the importance of understanding meteorological conditions and predicting the weather, as well. An analysis of existing studies in meteorology reveals that this field received little or no attention from language or communication perspectives, although we believe it is essential for both specialists and different types of audience to send and understand messages easily and take action accordingly. The aim of this paper is to present a state-of-the-art analysis of different language and communication approaches to meteorology, and to come up with a series of recommendations on possible directions of research in the field.